Design and Implementation of a Patient Monitor via the Internet - Jawad, Ameer Shuail; Ahmad, Lbrahim Shihab; Nasser, Hussein Dawood Jassim; Halou, Ali Abdul Hussein; salih, Muamal luay (American Journal of Botany and Bioengineering, 2025)
The summary of this work is the research that was conducted to assist the doctor and nurse in order to help them follow up on the patient’s condition and vital activities, where the doctor or nurse can monitor and follow up on the patient without the need to go to the patient. Patient health monitoring system using ESP8266 and Arduino: With the existence of emerging industries arising from modern industries in the field of food industries. Implementation of previous actions platform more than other things in this project. ThingSpeak is an open source Internet of Things (IoT) implementation and API that sends data from the Internet over the Internet or over a local area network. The following computer can read the pulse rate and measure the ambient temperature thermometer. Continuously monitors pulse rate and ambient temperature. It runs the Arduino Sketch software that performs the various tasks of the project such as reading the sensor data and converting it to the IoT platform and the pulse width and temperature measured on the character LCD. Health monitoring is the main problem in today’s world. Due to the lack of proper health monitoring, the patient has serious health problems. There are a lot of IoT devices to monitor patient health online. Health experts are also making use of these smart devices to monitor their patients. With so many new startups in the field of healthcare technology, the Internet of Things is rapidly revolutionizing the healthcare industry. Here in this project, we will create an IoT based health monitoring system that records patient’s heart rate, body temperature and also sends an email/SMS alert when these readings exceed critical values. Pulse rate and body temperature readings are recorded in Thing Speak and Google Sheets so that the patient’s health can be monitored from anywhere in the world via the Internet. A panic note will also be attached so that the patient can press it in emergency situations to send email/SMS to their relatives.